Service-learning in problem solving in the community: pre-service teachers’ reflection on their experience - Lenkauskaitė, Jurgita (Social Welfare: Interdisciplinary Approach, 2020)
The article substantiates the relevance of service-learning in the study process of pre-service teachers solving problems relevant to the community. The multifaceted benefits of service-learning for both learners and the community have been highlighted. Pre-service teachers treat the service-learning experience as unique, allowing them to get closely acquainted with professional reality, develop collaboration outside the university, understand the importance of change in education in response to the needs of society and the extent of their responsibility for this change.